A Critique of Search and Seizure in Terms of a Search Warrant in South African Criminal Procedure: A Comparative Analysis. Issue 4 (November 2019) - Basdeo, Vinesh
Abstract : The primary objective of this article is to determine whether the search and seizure measures employed in the South African criminal justice system are in need of any reform and/or augmentation in accordance with the 'spirit, purport and object' of the Constitution. This article analyses 'search and seizure' in the South African criminal justice system as is made possible by Chapter 2 of the Criminal Procedure Act 51 of 1977, which provides for search warrants, the entering of premises, and the seizure, of property connected with offences. It determines whether the required judicial scrutiny provides a real control upon the exercise of search and seizure powers. Search and seizure legal principles extracted from American criminal procedure will also be analysed for comparative purposes.